The Role of Freight Forwarding Services in Supporting Export Activities in PT Citra Trans Buana Kargotama Jakarta - Dewi Tati; Furi Indriyani; Ade Kurniawati; Ida Hendarsih (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The purpose of this study was to obtain a deeper description and understanding of the role of Freight Forwarding in supporting export activities at PT Citra Trans Buana Kargotama Jakarta. This research was conducted using a qualitative descriptive method, which is a problem formulation that guides research to explore and describe what will be studied thoroughly, broadly, and deeply. and The data used in this study is primary data obtained through direct interviews with PT Citra Trans Buana Kargotama Jakarta. Based on the results of research on export activity procedures at PT Citra Trans Buana Kargotama Jakarta, namely from exporters sending Shipping Instructions to PT Citra Trans Buana Kargotama Jakarta and then to DHL Express (couriers). While the parties and agencies directly related to PT. Citra Trans Buana Kargotama Jakarta is an exporter, importer, agent of freight forwarder, customs, shipping company, trucking company, and container depot. And in terms of export procedures at PT. Citra Trans Buana Kargotama Jakarta, the documents that must be fulfilled in the procedure for shipping goods are a packing list, invoice, shipping instruction, bill of loading, certificate of origin, notification of export of goods, and certificate of fumigation.